Efforts to Improve the Ability to Recognize Numbers 1-10 by Using Associative Media in Children in Kindergarten - Ranti Kartalena; Manto Manto (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to improve the ability to recognize numbers 1-10 by using associative image media in TK Satu Atap Empat Lawang. Number recognition skills include calling numbers, matching numbers with associative images, and writing numbers. The purpose of this study is to describe the planning, implementation, and evaluation of learning in an effort to improve the ability to recognize numbers 1-10 using associative image media in TK Satu Atap Empat Lawang. The approach used in this study is qualitative, and the type of research is descriptive qualitative. Data collection techniques include interviews, observation, and documentation. Data analysis uses data condensation, data presentation, and conclusions. The validity of the data in this study used source triangulation and triangulation techniques.